Strengthening Cultural Understanding and Local Wisdom through a Cultural Literacy Program at SMA YPK Medan - Darmawati Darmawati; Muhmmad Ali Hadidie Parinduri (STIKES Columbia Asia Medan, 2025)
This community service program focuses on strengthening cultural literacy and local wisdom understanding among students at SMA YPK Medan. The aim was to foster a deeper appreciation of local culture, values, and traditions, integrating them into the educational process to support sustainable cultural preservation. The program involved participatory methods, including workshops, cultural discussions, and creative student projects that showcased the students' interpretations of local heritage. The initiative was designed to bridge the gap between traditional knowledge and modern education, promoting active student engagement and raising awareness of the importance of cultural heritage. The involvement of local community leaders, educators, and the school administration was pivotal in ensuring the success of the program. Results showed increased student enthusiasm towards local culture, as well as a heightened sense of pride and responsibility towards preserving it. The program's potential for sustainability lies in its integration into the school curriculum and its scalability to other educational institutions.